As We May Ink? Learning from Everyday Analog Pen Use to Improve Digital Ink Experiences - Riche, Yann; Henry Riche, Nathalie; Hinckley, Ken; Fuelling, Sarah; Williams, Sarah; Panabaker, Sheri (Proceedings of ACM SIGCHI conference, 2017)
This paper sheds light on gaps and discrepancies between the experiences afforded by analog pens and their digital counterparts. Despite the long history (and recent renaissance) of digital pens, the literature still lacks a comprehensive survey of what types of marks people make and what motivates them to use ink—both analog and digital—in daily life. To capture the diversity of inking behaviors and tease out the unique affordances of pen-andink, we conducted a diary study with 26 participants from diverse backgrounds. From analysis of 493 diary entries we identified 8 analog pen-and-ink activities, and 9 affordances of pens. We contextualized and contrasted these findings using a survey with 1,633 respondents and a follow-up diary study with 30 participants, observing digital pens. Our analysis reveals gaps and research opportunities based on pen affordances not yet fully explored in the literature.